Pathogenic variability and effect of culture filtrate of Sclerotium oryzae on the inhibition of radicle and plumule in rice - R.A. SINGH, Z. ALI* and (Indian Phytopathology, 2002)
Relative virulence of 15 isolates of the pathogen (S. oryzae) was tested on six differentials by inoculation under glasshouse and laboratory conditions. In the glasshouse stem wrap method (SWM) and under laboratory conditions. the cut stem wound (CSW) inoculation method were followed. On the basis of disease reaction on the differntials, the isolates have been divided into six categories. Rice cv. Pant Dhan 4 was selected to study the effect of culture filtrate on radicle and plumule length with a view to find differences in the toxin production among the isolates, if any. Culture filtrate of all the isolates inhibited the radicle and plumule elongation which was directly correlated with the concentration of the culture filtrate in comparison to check. The maximum inhibition of radicle and plumule occurred in undiluted culture filtrate followed by 50 and 25 per cent filtrate.